МОДЕЛЮВАННЯ РЕЖИМІВ ЕНЕРГОМОСТА УКРАЇНА – ЄВРОСОЮЗ - Сегеда, М.С.; Покровський, К.Б.; Маврін, О.І.; Олійник, В.П. (Інститут електродинаміки Національної академії наук України, 2019)
The power bridge of Ukraine – EU model for static regimes and transient processes for variants of the scheme is developed in software environment of Power Factory v.15.2 based on a set of model network elements. The mathematical model is tested on the results of control measurements. The influence of excess reactive power in the network scheme on the coordinates of the modes and relatively low efficiency of shunt reactors for its compensation in conditions of application of the synchronous generator is shown. The use of an asynchronized generator for increasing the efficiency of the scheme is proposed.  References 7, figures 5, table.